Beyond Words: Uncovering the Untold Stories of Multilingual Students' Lived Experiences in Online Distance Learning - Melvin T Guache; Karen A Manaig; John Federick Tesoro; Albert D Yazon; Sherwin B Sapin (Journal of Elementary and Secondary School, 2023)
This study aimed to examine the lived experiences of multilingual students in online distance learning during the height of the COVID-19 pandemic. The study utilized the qualitative research design - transcendental phenomenology and employed purposive sampling. The study participants were ten (10) multilingual students among Senior High School Students. A researcher-made questionnaire was reviewed by research experts and was used in individual interviews with the participants. The collected data through interviews underwent thematic analyses and triangulation. Based on the findings, the model was developed through thematic analyses, the Basic Instructional Strategies Aiming to Address the Problems of Multilingual Students in Online Distance Learning MODEL (in the Filipino language: Batayang Instruksiyong estratehiya na Naglalayong Tugunan at Alamin (BINTA) ang mga suliranin ng mga multilinggwal na mag-aaral sa online distance learning) was developed. The BINTA Model represents the lived experiences of multilingual students in online distance learning in terms of the themes that emerged: lack of interaction and communication, difficulty in understanding technical terms, consistency of internet connection, and effective communication. This implies that the model can help improve these students' educational outcomes and experiences by providing appropriate instructional strategies tailored to the needs of multilingual students. Educators can help mitigate these students' challenges and difficulties in an online distance learning environment. Through this, educators can help ensure that multilingual students can engage with the material, participate fully in online discussions and activities, and ultimately achieve their learning goals.